Pembelajaran Sharf sebagai Dasar Memahami Al-Qur’an: Workshop Interaktif bagi Muslimah di MTMB Lhokseumawe - Hayati, Ulfi; Ediyani, Muhammad; Husaini, Husaini (LSM Catimore dan Sahabat, 2024)
The Qur'an and Arabic are integral parts of acquiring knowledge. The rise of the study of the Qur'an, makes sharf must be taught to the Majlis Ta'ilm Muslimah Baiturrahman Mosque. The purpose of this devotion is for Muslim women to be able to explain the change in Arabic fi’il and identify the form of fi'il change in the Qur'anic verse. The method used is qualitative with lectures, discussions and evaluations as the workshop agenda and observation as the instrument. The result obtained that this devotion went successfully and smoothly. It is shown that knowledge of changes in verb structure can be learned and characterized by changes in patterns in each dhamir, so that this becomes a reference in finding fi'il in the verses of the Qur'an and increases piety in learning Arabic and the Qur'an.